2011
DOI: 10.1136/gut.2011.239301.150
|View full text |Cite
|
Sign up to set email alerts
|

Faecal calprotectin as part of standardised assessment tool of suspected irritable bowel syndrome (IBS): a novel investigative algorithm

Abstract: Introduction There is enormous variability in the referral rates for IBS from GPs and this relates to patient and physician factors. 1 IBS patients tend to wait longer for appointments and hence a standardised algorithm which includes faecal calprotectin (FC) might aid in the rapid assessment of IBS in secondary care. FC has been shown to consistently differentiate IBS from IBD because it has excellent negative predictive value in excluding organic pathology. 2 Methods To assess the effi cacy of diagnostic alg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…And in a recent meta-analysis it had been concluded that measuring ‘faecal calprotectin is a useful screening tool for identifying patients who are most likely to need endoscopy for suspected IBD.’9 The authors however expressed reservations about its utility in primary care. To date, no studies have been performed in the primary care setting to refute this 10 11…”
Section: Discussionmentioning
confidence: 99%
“…And in a recent meta-analysis it had been concluded that measuring ‘faecal calprotectin is a useful screening tool for identifying patients who are most likely to need endoscopy for suspected IBD.’9 The authors however expressed reservations about its utility in primary care. To date, no studies have been performed in the primary care setting to refute this 10 11…”
Section: Discussionmentioning
confidence: 99%
“…The Cardiff data show that a considerable proportion of referrals by GPs are to confirm IBS (by exclusion of IBD). 38 So the main value of calprotectin testing may be to confirm presumptive diagnoses of IBS, and that can be done in general practice. Other studies (Rotherham unpublished) report that > 60% of colonoscopies in the 'pre-calprotectin era' showed no pathology.…”
Section: Use Of Calprotectin In Routine Carementioning
confidence: 99%
“…In one small study (54 patients) from Cardiff, the main reason for referral was diagnostic uncertainty (37/54) but the second reason was for 'confirmation of IBS' (17/54). 38 In various studies, the proportion of patients referred for further investigation, in whom abnormal findings are reported on colonoscopy, is low. Kok et al 39 noted reports that only 22-37% had organic bowel disease (OBD).…”
Section: Introductionmentioning
confidence: 99%